Felsic Melt and Gas Mobilization During Magma Solidification: An Experimental Study at 1.1 kbar - Pistone, Mattia; Baumgartner, Lukas P.; Bégué, Florence; Jarvis, Paul A.; Bloch, Elias; Robyr, Martin; Müntener, Othmar; Sisson, Thomas W.; Blundy, Jon D. (Frontiers in Earth Science, 2020)
Melt and gas transfer processes are essential to the formation and growth of the Earth’s crust and for sustaining volcanic activity. These processes also play a major role in magma fractionation at shallow depths (< 10 km) where magmas stall rheologically and solidify. In this scenario, the conditions of melt and gas mobilisation during progressive cooling of crystal mushes down to their solidus remain poorly understood. We present experimental data (at 1.1 kbar) showing how a combination of temperature and crystal content control the ability of melt and gas to escape from cooling and solidifying hydrous silicic magmas with initial crystal fractions of 0.6, 0.7, and 0.8, and for temperature snapshots of 850, 800, and 750 °C. Microstructural observations and chemical data show that the amount of extracted melt increases by 70% from 850 to 750 °C and by 40% from 0.6 to 0.8 in crystal fraction at 750 °C, due to the formation of interconnected crystal frameworks, gas expansion in constricted pore space, and filter pressing during cooling. As a result, our experiments suggest that melt and gas extraction from cooling mushes increases in proximity to their solidus and can operate efficiently at crystal fractions between 0.6 and 0.93. These observations shed light on maximum estimates of the segregation of gas-rich, crystal-poor magmas (0.02 m/year at 850 °C to 9 m/year at 750 °C) to form felsic dykes or eruptible systems feeding volcanoes.